Valorization of Research and Scientific Innovation Results as Factor of Sustainable Development of African Agriculture: the Example of Burkina Faso - Banhoro, Abdoulazize; Nana, Rasmata; Ouedraogo, Mahamadi Hamed; Sawadogo, Mahamadou (Afrika Focus, 2019)
During the 1980s, many development partners in Africa were preoccupied by the application of research results to agricultural development. In Burkina Faso, this awareness led to set structures and mechanisms for the promotion of research results. From the synthesis of critical analyses of the valorization system, it appears that the valorization concept is polysemous. In addition, there has been strong evolution in the mechanisms for promoting research results, development has also been hampered by certain shortcomings. Thus we propose, as a main track for a successful valorization policy, the creation of start-ups constituted of young professionals who possess skills that are specific and complementary. Young university-educated professionals are equipped to understand the new technologies of production and agricultural transformation. With an effective management plan the start-ups they represent could foster an effective application of research results, to improve food security and enhance the competitiveness of Burkina’s agricultural products on international markets. KEY WORDS: VALORIZATION, POLYSEMOUS, START-UP, AGRICULTURE